2021
DOI: 10.3389/fphar.2021.733618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Therapeutic Mechanisms of Selected Active Compounds in Houttuynia cordata Thunb. in Pulmonary Fibrosis via Network Pharmacology Analysis

Abstract: Pulmonary fibrosis, a common outcome of pulmonary interstitial disease of various different etiologies, is one of the most important causes of respiratory failure. Houttuynia cordata Thunb. (family: Saururaceae) (H. cordata), as has been reported, is a Chinese herbal medicine commonly used to treat upper respiratory tract infection and bronchitis. Our previous study has proven that sodium houttuyfonate (an additional compound from sodium bisulfite and houttuynin) had beneficial effects in the prevention of pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Our previous network pharmacology study of H. cordata Thunb. identified that it may act through multiple signaling pathways to alleviate PF (Zhu et al, 2021). Our in vivo experimental study also clarified that sodium houttuyfonate, an adduct compound of houttuynin and sodium bisulfite, may alleviate the degree of fibrosis in bleomycin-induced PF model mice through the transforming growth factor-β (TGF-β)/Smads pathway (Shen et al, 2021).…”
Section: Discussionmentioning
confidence: 61%
“…Our previous network pharmacology study of H. cordata Thunb. identified that it may act through multiple signaling pathways to alleviate PF (Zhu et al, 2021). Our in vivo experimental study also clarified that sodium houttuyfonate, an adduct compound of houttuynin and sodium bisulfite, may alleviate the degree of fibrosis in bleomycin-induced PF model mice through the transforming growth factor-β (TGF-β)/Smads pathway (Shen et al, 2021).…”
Section: Discussionmentioning
confidence: 61%
“…Pharmacological networks have predicted that Qimai feiluoping decoction exerts anti-PF effects via regulation of the epithelial-mesenchymal transition, extracellular matrix degradation, and TGF- β signaling pathway, and this has been verified in vitro [ 31 ]. Pharmacological networks have also found that Chinese herbs such as Curcuma Radix [ 32 ], Houttuynia cordata [ 33 ], Schisandra [ 34 ], and Astragalus can regulate PF via the TGF- β , PI3K/Akt, MAPK, and STAT3 signaling pathways. Astragalus is the most popular Chinese herb for supplementing Qi and is the main ingredient of the representative Buyang Huanwu decoction that also activates blood circulation.…”
Section: Discussionmentioning
confidence: 99%
“…(2014) Anti-viral Pang et al. (2017) Anti-pulmonary fibrosis Zhu et al. (2021) Anti-fungal ( Candida albicans ) Shao et al.…”
Section: Chemical Constituents Of H Cordatamentioning
confidence: 99%